PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA KEUANGAN PADA PT PLN (PERSERO) AREA MAKASSAR SELATAN - Muhammad Ikram Idrus; Faidhul Adziem; Hasri Nayun (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the effect of the use of information technology on financial performance at PT. PLN (Persero) South Makassar Area. This type of research is an empirical research method of collecting data using a questionnaire with a sample of 32 respondents of PT. PLN south Makassar area. Data analysis using multiple regression analysis techniques with SPSS software is used to test the research hypothesis. The results showed that the simultaneous use of information technology had a significant effect on financial performance. The use of information technology persistently affects financial performance.This study aims to determine the effect of the use of information technology on financial performance at PT. PLN (Persero) South Makassar Area. This type of research is an empirical research method of collecting data using a questionnaire with a sample of 32 respondents of PT. PLN south Makassar area. Data analysis using multiple regression analysis techniques with SPSS software is used to test the research hypothesis. The results showed that the simultaneous use of information technology had a significant effect on financial performance. The use of information technology persistently affects financial performance.